Ekonomia społeczna i program samopomocy społecznej w projektach ekonomicznych Zygmunta Herynga - Sikorska-Kowalska, Marta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
Zygmunt Heryng was an economist, a politican, a social and educational activist. The brochure Samopomoc społeczna jako jedyna dla nas deska ratunku (Social aid as our only chance) was written at the inflation time and growing economic crisis at the beginning of the 20th century. Z. Heryng took part in a discussion concerning the protection of the poorest. In his view the only chance to in prove the conditions of live of the poor was in the development of cooperative movement supported by the government. He presents a detailed program addressed to the members of the cooperative movement, legislators and the government. In his paper he presents his views concerning social economics. Social economics is very important branch of economics in contemporary time, it originates from the beginning of the 19th century.